Grain orientation dependent Nb–Ti microalloying mediated surface segregation on ferritic stainless steel. (November 2016) - Ali-Löytty, Harri; Hannula, Markku; Honkanen, Mari; Östman, Kauko; Lahtonen, Kimmo; Valden, Mika
Graphical abstract: Highlights: Competitive surface segregation of Si, Nb and Ti occurs above 550 °C. Surface segregation is favored to the 〈111〉 oriented grains. Surface segregation of Cr is limited at the Ti/Nb precipitate locations. The optimization of microstructure facilitates the fast growth of protective scale. Abstract: Surface segregation and oxide formation anisotropy on Ti–Nb stabilized ferritic stainless steel (EN 1.4521) were studied by XPS and Electron Backscatter Diffraction. Competitive surface segregation of Si, Nb and Ti was initiated at ∼550 °C, and segregation was favored to the open surface sites of 〈111〉 oriented grains. Furthermore, the surface segregation of Cr was strongly limited at the locations of stable Ti(CN)- and (NbTi)C-type precipitates. Consequently, the oxidation resistance of stainless steels can be enhanced cost-efficiently, without alloy additions, by optimizing the microstructure to facilitate the fast and uniform growth of protective oxide scale.